Multiscale Coupling of Pore Structure Evolution with Decomposition Kinetics of Limestone. Issue 10 (10th September 2015) - Li, Mingchun; Song, Lanting; Wu, Yusheng; Noël, Timothy; Hessel, Volker
Abstract The pore structure evolution and reaction characteristics of limestone with different particle sizes during thermal decomposition were investigated experimentally. A kinetic model considering the effect of pore structure evolution was developed to simulate the multiscale coupling of the mesoscale pore structure with the macroscopic transport and microscopic chemical reaction. Over a defined particle size range, the calculated results were in good agreement with the experimental data including the influence of gas diffusion throughout the whole decomposition course. A dimensionless Thiele modulus Th was constructed for assessing the critical point corresponding to the transformation of controlled mechanisms.